Soft Bottom Molluscan Assemblages of the Bathyal Zone of the Sea of Marmara - DOĞAN, A.; ÖZTÜRK, B.; BİTLİS-BAKIR, B.; TÜRKÇÜ, N. (Mediterranean Marine Science, 2016)
The present study deals with the soft bottom molluscan species collected from the bathyal zone of the Sea of Marmara in 2013. Replicated samples were taken by a Box Core, sampling an area of 0.1 m2 at 31 stations at the two depth transects, 500 and 1000 m. A total of 1229 individuals belonging to 4 classes and 28 species were collected. Two species (Akritogyra conspicua and Liostomia hansgei) are new records for the marine molluscan fauna of Turkey and four species (Benthonella tenella, Odostomia silesui, Syrnola minuta and Crenilabium exile) are new records for the molluscan fauna of the Sea of Marmara. A relatively richer fauna was determined in 500 m (25 species) than in 1000 m (17 species). The most dominant species at 500 m and 1000 m depths were Crenilabium exile and Parthenina flexuosa, respectively. Number of species and number of individuals varied significantly only between depths while number of individuals changed significantly among basins (ANOVA test). A significant difference in species assemblages between the Tekirdağ and the Central Basins was detected (ANOSIM test). The multivariate analysis showed that the depth was the main factor influencing the molluscan assemblages in the area.